Synthesis and evaluation of antimycobacterial activity of new benzimidazole aminoesters - Yoon, Y.K.; Ali, M.A.; Wei, A.C.; Choon, T.S.; Ismail, R. (Elsevier, 2015)
Abstract A total of 51 novel benzimidazoles were synthesized by a 4-step reaction starting from basic compound 4-fluoro-3-nitrobenzoic acid under relatively mild reaction conditions. The structure of the novel benzimidazoles was confirmed by mass spectra as well as 1H NMR spectroscopic data. Out of the 51 novel synthesized compounds, 42 of them were screened for their antimycobacterial activity against Mycobacterium tuberculosis H37Rv strain using BacTiter-Glo™ Microbial Cell Viability (BTG) method. Results of activity screened using Alamar Blue method was also provided for comparison purposes. Two of the novel benzimidazoles synthesized showed moderately good activity with IC50 of less than 15 μM. Compound 5g, ethyl 2-(4-(trifluoromethyl)phenyl)-1-(2-morpholinoethyl)-1H-benzo[d]imidazole-5-carboxylate, was found to be the most active with IC50 of 11.52 μM.